An Efficient Ultrasound‐Assisted Synthesis of N‐Alkyl Derivatives of Carbazole, Indole, and Phenothiazine. (2nd December 2013) - Zhao, Sanhu; Kang, Jin; Du, Yuting; Kang, Jingyan; Zhao, Xiaoni; Xu, Yinfeng; Chen, Ruixi; Wang, Qianqian; Shi, Xitao
<x xml:space="preserve">Abstract</x> Heterocyclic compounds bearing an acidic hydrogen atom attached to nitrogen such as carbazole, indole, and phenothiazine can be efficiently alkylated in DMSO or N, N‐DMF under ultrasonic irradiation in the presence of potassium hydroxide as a base. In almost all cases, a dramatic reduction of the reaction time results and a clear yield increase accompanied by an improved quality of the products occurs.